Operational Management Readiness in Enhancing Customer Satisfaction (A Case Study of PT. Cipta Karya Technology in Medan City) - Sihotang, Mhd Rifani; Nasution, Muhammad Syukri Albani (Majapahit Journal of Islamic Finance and Management, 2025)
The advancement of information and communication technology has intensified the demand for fast and stable internet services. Consequently, internet service providers (ISPs), particularly those offering WiFi services, must strengthen their operational management readiness to meet customer expectations. This study aims to analyze the extent to which operational management readiness contributes to enhancing customer satisfaction among WiFi internet service users in a private company. The findings indicate that strong operational management readiness significantly improves customer satisfaction by enhancing service quality, reducing waiting times, and improving accessibility. Therefore, ISPs should prioritize operational management readiness as a strategic component to increase customer satisfaction and sustain competitive advantage.